Value of ultrasound for access guidance and detection of subclinical vascular complications in the setting of atrial fibrillation cryoballoon ablation. Issue 3 (11th July 2018) - Ströker, Erwin; de Asmundis, Carlo; Kupics, Kaspars; Takarada, Ken; Mugnai, Giacomo; De Cocker, Jeroen; Stockman, Dirk; Sieira, Juan; Schwagten, Bruno; Brugada, Pedro; De Greef, Yves; Chierchia, Gian Battista
Abstract: Aims: Vascular complications are the most common complications of atrial fibrillation (AF) ablation. Cryoballoon (CB) ablation for AF needs the insertion of a large 15 Fr sheath in the femoral vein. Our aim was to investigate the impact of vascular ultrasound (US) in guiding access and evaluating post-procedural subclinical complications in a large, multi-centre patient cohort that underwent CB ablation. Methods and results: A total cohort of 1435 consecutive patients were subdivided in 870 US −/−, 265 US −/+, and 300 US +/+ patients depending on US performance for: venipuncture guidance/post-procedural evaluation. Major clinical complications (requiring intervention and/or prolonged stay) were assessed. Irrespective of the clinical status, major US events were systematically determined in the subgroups with US evaluation 1 day post-procedure, if evidence of inadvertent artery puncture/cannulation (communication between artery and collection or artery-vein, regardless of the thrombosis state). Major clinical events were encountered in 1.7% (15/870), 1.1% (3/265), and 0% of patients in US −/−, US −/+, and US +/+ group, respectively ( P  =   0.02 between US −/− and US +/+ group). In the US −/− group, 5/10 (50%) of pseudo-aneurysms were diagnosed during readmission after a mean of 24 ± 11 days post-procedure. No delayed presentation was seen in the US −/+ group. Major US events during the US protocol post-procedure were seen in 3.8% (10/265) vs. 0.3% (1/300) of patients in US −/+ vs. US +/+ group, respectively, P =  0.004. Conclusion: US-guided venipuncture was associated with a near-to-zero risk of vascular complications in our patients undergoing CB ablation.